1987
DOI: 10.1016/0309-1651(87)90134-2
|View full text |Cite
|
Sign up to set email alerts
|

Immunofluorescent localization of protein synthesis components in mouse embryo fibroblasts

Abstract: The distribution of initiation factor 2(eIF-2) and elongation factor 2(EF-2) in cultured mouse embryo fibroblasts was studied and compared with the distribution of ribosomes. We used immunofluorescence microscopy with monospecific antibodies to eIF-2, EF-2, and proteins S3a and S7 of the small ribosomal subunit. Ribosomes and factors eIF-2 and EF-2 were found mainly in the vicinity of the cell nucleus. This perinuclear zone coincides with the endoplasm - the central part of the cell containing numerous membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 16 publications
3
23
0
Order By: Relevance
“…1C) and LC-MS/MS (Table III), EF-1␣ (spot 38) was an abundant protein in the tubulin-binding protein fraction. Several other elongation and initiation factors were also identified, some of which have been shown to bind to MTs and other cytoskeletal structures in previous studies (Table III) (12,(43)(44)(45)(46). These included EF-2 (spot 4) and subunits of the eukaryotic translation initiation factors eIF3 and eIF4 (spots 7,18,24,27,50,54,70).…”
Section: Resultsmentioning
confidence: 78%
“…1C) and LC-MS/MS (Table III), EF-1␣ (spot 38) was an abundant protein in the tubulin-binding protein fraction. Several other elongation and initiation factors were also identified, some of which have been shown to bind to MTs and other cytoskeletal structures in previous studies (Table III) (12,(43)(44)(45)(46). These included EF-2 (spot 4) and subunits of the eukaryotic translation initiation factors eIF3 and eIF4 (spots 7,18,24,27,50,54,70).…”
Section: Resultsmentioning
confidence: 78%
“…Fifteen percent to 30% of cellular mRNAs and polyribosomes are thought to associate with the cytoskeleton, and immunohistologic and biochemical approaches suggest that translation initiation and elongation factors in certain cell types follow a microtubule pattern (33). Examples of proteins that regulate translation and that associate with microtubules include eIF-2, eIF3, eIF4A, eIF-5 (34)(35)(36), the cap-binding protein eIF4E (37), eEF1a, and eEF1-2 (35). Using molecular beacons specific for HIF-1a mRNA, we observed microtubule association of HIF mRNA, which was disrupted following treatment with microtubule-depolymerizing Figure 4.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that protein synthesis in mammalian cells occurs in a "channeled pathway," in which many of the components of the synthetic machinery are spatially restricted, such that individual components are directly transferred to the translational complex without dissociating into the soluble phase of the cytoplasm (Negrutskii et al, 1994). In accordance with these findings, a number of proteins that are involved in translational regulation, including the cap-binding protein (Zumbe et al, 1982), translation initiation factors eIF-2, eIF3, eIF4A, and eIF-5 (Howe and Hershey, 1984;Gavrilova et al, 1987;Heuijerjans et al, 1989), and elongation factors eEF1␣ (Yang et al, 1990) and eEF1-2 (Gavrilova et al, 1987) have been found associated with the cytoskeleton. Other proteins involved in posttranscriptional regulation such as poly A ϩ -binding protein (Greenberg, 1980) and seryl-tRNA synthetase (Miseta et al, 1991) can be found UV crosslinked to the mRNA in vivo.…”
Section: Discussionmentioning
confidence: 94%